Diminished impact of cytomegalovirus infection on graft vasculopathy development in the antiviral prophylaxis era – a retrospective study. (16th April 2018) - Goekler, Johannes; Zuckermann, Andreas; Kaider, Alexandra; Angleitner, Philipp; Osorio‐Jaramillo, Emilio; Moayedifar, Roxana; Uyanik‐Uenal, Keziban; Kainz, Frieda‐Marie; Masetti, Marco; Laufer, Guenther; Aliabadi‐Zuckermann, Arezu Z.
Summary: Evidence concerning an association between cytomegalovirus (CMV) infection and accelerated cardiac allograft vasculopathy (CAV) is inconclusive. Data were analyzed retrospectively from 297 consecutive heart transplants between 1.1.2002 and 31.12.2012. Patients ≤18 years of age, survival, and follow‐up ≤1‐year post‐transplant and patients with early CAV were excluded. CMV‐infection was diagnosed and monitored closely in the first year. CAV was diagnosed by coronary angiography via left heart catheterization, and results were categorized according to the International Society of Heart and Lung Transplantation (ISHLT) scoring system. Risk factors for CAV were tested in a multivariable model. Median follow‐up was 7.5 years (IQR: 5.6–10.3). CMV infection in the first year after transplantation occurred in 26% of patients ( n = 78), CMV disease in 5% ( n = 15). CAV ≥1 ISHLT was detected in 36% ( n = 108). Incidence of CAV >1 ISHLT and severity of CAV increased over time. No statistically significant association between CMV infection and disease within the first year and risk of CAV after 1‐year post‐HTx was detected in the univariate ( P = 0.16) and multivariable [hazard ratio (HR), 1.36; confidence interval (CI), 0.89–2.07; P = 0.16] Cox regression. In the multivariable Cox regression, donor age (HR, 1.04; 95% CI, 1.02–1.06; P < 0.01) and acute cellular rejection (ACR) ≥2R in the first year after HTx (HR, 1.77; 95% CI, 1.06–2.95; P = 0.03) were independent risk factors for CAV development. In our cohort, CMV infection and disease in the first year after transplantation did not significantly influence the risk of CAV in the long‐term follow‐up.